1993
DOI: 10.1080/00207149308414534
|View full text |Cite
|
Sign up to set email alerts
|

The Carleton Skills Training Package for Modifying Hypnotic Susceptibility - a Replication and Extension: A Brief Communication

Abstract: This study employed the Carleton Skills Training Package (CSTP) to attempt to enhance both objective and subjective components of hypnotic susceptibility. In addition, changes in susceptibility were compared for subjects administered a standard hypnotic induction procedure and for subjects given brief "place yourself in hypnosis" instructions. Results indicated that subjects who were administered the CSTP exhibited significant gains in both objective and subjective susceptibility scores that were maintained at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

1993
1993
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 15 publications
(14 reference statements)
0
7
0
Order By: Relevance
“…Subjects after training demonstrated incremental change on both the objective and subjective dimensions of the standardized scale of hypnotic susceptibility, but the gains obtained in the present study were smaller than those reported by the researchers from Carleton University (Gorassini & Spanos, 1986a;Spanos, Robertson, et al, 1987) and comparable to results obtained in other laboratories (Bates et. al., 1988;Bates & Brigham, 1990;Bertrand et al, 1993;Gfeller et al, 1987). In Spanos's studies, hypnotic susceptibility at the time of pretest and posttest was assessed with the Carleton University Responsiveness to Suggestion Scale (CUES; Spanos, Radtke, Hodgins, Bertrand, Stam, & Dubreuil, 1983).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Subjects after training demonstrated incremental change on both the objective and subjective dimensions of the standardized scale of hypnotic susceptibility, but the gains obtained in the present study were smaller than those reported by the researchers from Carleton University (Gorassini & Spanos, 1986a;Spanos, Robertson, et al, 1987) and comparable to results obtained in other laboratories (Bates et. al., 1988;Bates & Brigham, 1990;Bertrand et al, 1993;Gfeller et al, 1987). In Spanos's studies, hypnotic susceptibility at the time of pretest and posttest was assessed with the Carleton University Responsiveness to Suggestion Scale (CUES; Spanos, Radtke, Hodgins, Bertrand, Stam, & Dubreuil, 1983).…”
Section: Discussionmentioning
confidence: 99%
“…After administering the procedure, which was designed by Donald R. Gorassini and Nicholas P. Spanos (1986a) at Carleton University, 50% to 80% of the subjects initially minimally unresponsive to hypnotic suggestions scored in the high range of the standardized scales of hypnotic susceptibility (Gorassini & Spanos, 1986a;Spanos, Cross, Menary, Brett, & de Groh, 1987;Spanos, de Groh, & de Goot, 1987;Spanos, Robertson, Menary, Brett, & Smith, 1987). The researchers who replicated studies on the CSTP outside Carleton University usually obtained a smaller increase (Bates & Brigham, 1990;Bates, Miller, Cross, & Brigham, 1988;Bertrand, Stam, & Radtke, 1993;Gfeller, Lynn, & Pribble, 1987). The effects of the CSTP generalized to difficult novel suggestions that were not included in the training procedure (Gfeller et al, 1987;Gorassini & Spanos, 1986a;Spanos et al, 1995;Spanos & Flynn, 1989;Spanos, Flynn, & Gabora, 1993;Spanos, Lush, & Gwynn, 1989) and did not diminish with time (Spanos, Cross, Menary, & Smith, 1988;Spanos, Dubreuil, & Gabora, 1991).…”
Section: Goal-directed Fantasy Does Not Explain the Training Effect Omentioning
confidence: 98%
“…6, this volume), was used and self-reports about subjective states, especially about involuntariness, were elicited. These studies typically demonstrated significant, and usually large, increases in hypnotic experiencing in cognitivebehaviorally trained participants as compared with controls (Bates & Brigham, 1990;Bates & Kraft, 1991;Bates, Miller, Cross, & Brigham, 1988;Bertrand, Stam, & Radtke, 1993;Burgess, Dubreuil, Jones, & Spanos, 1991;Gearan & Kirsch, 1993;Gfeller, Lynn, & Pribble, 1987;Gorassini, 1995;Gorassini, Sowerby, Creighton, & Fry, 1991;Gorassini & Spanos, 1986;Spanos, Burgess, Roncon, Wallace-Capretta, & Cross, 1993;Spanos, Cross, Menary, Brett, & de Groh, 1987;Spanos, Cross, Menary, & Smith, 1988;Spanos, de Groh, & de Groot, 1987;Spanos, Flynn, & Niles, 1989Spanos, Lush, & Gwynn, 1989;Spanos, Robertson, Menary, & Brett, 1986;Spanos, Robertson, Menary, Brett, & Smith, 1987). This research indicates that securing unhypnotizable participants' cooperation, having them role play suggested responses, and getting them to construe the situation according to suggested stories result in the participants ably sustaining, over the course of a hypnotic session, the experience that they are undergoing suggested phenomena involuntarily.…”
Section: The Success Of Cognitive-behuvimul Trainingmentioning
confidence: 99%
“…With the aim to improve the hypnotic responsiveness a few studies attempted to enhance the hypnotizability through psychological (see Lynn 2004 for a review) and pharmacological approaches ( Bryant et al, 2012 ; Whalley & Brooks, 2009 ). For example, it was shown that that subjects initially scored as low hypnotizables became highs after receiving the Carleton Skills Training Program (CSTP; Bertrand et al 1993 ) and that administration of oxytocin increased the hypnotic responsiveness ( Bryant et al, 2012 ). More recently, the non-invasive brain stimulation (NIBS) techniques have been tested in this field as well.…”
Section: Introductionmentioning
confidence: 99%